(untitled) (Літератури світу: поетика, ментальність і духовність, 2016)
The article deals with the lattest genre forms which have appeared in drama at the end of the XX century. The representative examples of play-sequel (G. Gorin, B. Akunin, O. Shishkin, I. Vyrypayev. T. Słobodzianek, T. Różewicz), are considered. Features of its poetics are analyzed.